UV moisture curing adhesive for electronic components and preparation method thereof

By using polyurethane acrylate and isocyanate acrylic, UV moisture curing glue, the problem of reduced viscosity of UV moisture curing glue in existing technologies, and achieve higher fit stability and service life.

CN117987073BActive Publication Date: 2025-01-28DONGGUAN GAOTU NEW MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410155779.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-04
Publication Date
2025-01-28
Estimated Expiration
2044-02-04

AI Technical Summary

Technical Problem

In the long-term use of electronic components, the existing UV moisture curing glue has reduced its viscosity, resulting in a decrease in bonding stability and protection, thereby reducing the service life of electronic products.

Method used

The use of polyurethane acrylic and formal acrylic acid as the main ingredient, under the action of catalysts, light -induced agents, stabilizers, and acrylic monomers, prepare UV moisture curing glue that can stabilize cross -linking and solidified under ultraviolet and normal temperature conditions Essence

Benefits of technology

The UV moisture curing glue made has good stickiness and fit stability. It is not prone to adhesion unstable in long -term use, which significantly improves the service life of electronic products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004696987570000011
    Figure BDA0004696987570000011
  • Figure BDA0004696987570000021
    Figure BDA0004696987570000021
  • Figure BDA0004696987570000061
    Figure BDA0004696987570000061
Patent Text Reader

Abstract

The present application relates to the field of functional adhesive materials, and specifically discloses a UV moisture curing adhesive for electronic components and a preparation method thereof. A UV moisture curing adhesive for electronic components is prepared from the following raw materials in parts by weight: 25-45 parts of polyurethane acrylate, 6-15 parts of isocyanate acrylate, 30-50 parts of acrylate monomer, 3-8 parts of photoinitiator, 2-6 parts of stabilizer, 1-2 parts of dewatering agent, 0.1-0.6 parts of antioxidant and 0.05-0.2 parts of catalyst; preparation method: acrylate monomer, stabilizer and antioxidant are used to prepare mixture A; polyurethane acrylate is added to prepare mixture B; dewatering agent is added to prepare mixture C; isocyanate acrylate is added to prepare mixture D; photoinitiator and catalyst are added to prepare UV moisture curing adhesive. The preparation process of the present application is simple, and the prepared UV moisture curing adhesive has good cross-linking stability and good bonding stability to electronic components.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of functional adhesive materials, and more specifically, to a UV moisture curing adhesive for electronic components and a preparation method thereof. Background Art

[0002] As electronic products gradually move towards miniaturization, integration and multi-functions, the requirements for assembly precision and thinness of electronic components, such as display screens and chips, are becoming increasingly higher during the assembly process, and the requirements for the safety performance and stability of the assembled electronic products are also becoming increasingly higher.

[0003] Because UV moisture curing adhesive has good bonding stability, can be quickly cured at room temperature, and can also be stably cured in a humid environment, it is not demanding on the conditions of the place of use and has good convenience of use. Therefore, UV moisture curing adhesive is generally used in the assembly, bonding and protection of electronic components.

[0004] UV moisture curing adhesive is generally composed of moisture curing polyurethane resin, reactive monomers, photoinitiators and other additives, such as antioxidants. The reactive monomers and polyurethane resin are polymerized by the photoinitiator to obtain UV moisture curing adhesive. Although this UV moisture curing adhesive has good curing performance and initial adhesion performance, when electronic products are used for a long time, the electronic components are in operation for a long time, and the thin UV moisture curing adhesive film layer will have the problem of reduced adhesion, which reduces the bonding stability and protection of electronic components, thereby reducing the service life of electronic products. Summary of the invention

[0005] In order to solve the problem that the current UV moisture curing adhesive is used in electronic components, the long-term use will reduce the adhesion, reduce the bonding stability and protection of electronic components, and shorten the service life of electronic products, the present application provides a UV moisture curing adhesive for electronic components and a preparation method thereof.

[0006] In a first aspect, the present application provides a UV moisture curing adhesive for electronic components, which adopts the following technical solution:

[0007] A UV moisture curing adhesive for electronic components is prepared from the following raw materials in parts by weight:

[0008]

[0009]

[0010] By adopting the above technical scheme, the UV moisture curing adhesive prepared in the present application is suitable for thin and light electronic products, and can be cured under ultraviolet light and room temperature conditions. The UV moisture curing adhesive film formed by curing has a relatively moderate initial adhesion and good lasting adhesion. The bonded electronic components are not prone to unstable bonding during long-term use, thereby improving the service life of electronic products.

[0011] The molecules of polyurethane acrylate contain acrylic functional groups and urethane bonds. The UV moisture curing adhesive obtained by curing has the high wear resistance, adhesion, flexibility, high peel strength and excellent low temperature resistance of polyurethane after curing. It also has the optical properties and weather resistance of polyacrylate. The introduction of polyurethane acrylate into the UV moisture curing adhesive can polymerize with the acrylate monomer under the action of the photoinitiator to prepare a UV moisture curing adhesive with good adhesion. At the same time, isocyanate acrylate is added to the system. Isocyanate acrylate is an acrylate containing isocyanate active groups, which can produce good synergy with polyurethane acrylate. Under the action of stabilizer and catalyst, the prepared UV moisture curing adhesive absorbs moisture in the air to cross-link and cure at room temperature, and has good curing stability. The stabilizer can further improve the compounding stability of isocyanate acrylate and polyurethane acrylate. The UV moisture curing adhesive prepared in this way has good light curing and moisture curing properties. The UV moisture curing adhesive film formed after curing has good adhesion and good bonding stability to electronic components. The dehydrating agent has a good effect of bonding water molecules, thereby improving the stability of the prepared UV moisture curing adhesive. The antioxidant can improve the aging resistance of the prepared UV moisture curing adhesive and improve the service life.

[0012] Preferably, the isocyanate acrylate is prepared from the following raw materials in parts by weight:

[0013] 25-35 parts of diisocyanate

[0014] Hydroxyacrylate 10-20 parts

[0015] 2-4 parts of castor oil modified polyol

[0016] Polyethylene glycol diglycidyl ether 0.5-2 parts

[0017] Catalyst 0.05-0.15 parts

[0018] Inhibitor 0.02-0.08 parts.

[0019] Preferably, the isocyanate is one or more of hexamethylene diisocyanate, isophorone diisocyanate, 4,4-dicyclohexylmethane diisocyanate, xylylene diisocyanate and tetramethyl-meta-xylylene diisocyanate.

[0020] Preferably, the hydroxyacrylate is any one or more of hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate or hydroxypropyl methacrylate.

[0021] Preferably, the catalyst used in the preparation process of the isocyanate acrylate is an organic tin catalyst, and the inhibitor is any one of hydroquinone and p-hydroxyanisole.

[0022] By adopting the above technical scheme, in order to further improve the tackiness of the prepared UV moisture-curing adhesive, the present application uses diisocyanate to provide isocyanate active groups and hydroxy acrylate to provide active hydroxyl groups, and reacts under the action of a catalyst to prepare an acrylate containing an isocyanate group. During the reaction, castor oil-modified polyol and polyethylene glycol diglycidyl ether are added to the system. The castor oil-modified polyol has a flexible molecular chain segment and active reactive hydroxyl groups, and the polyethylene glycol diglycidyl ether has a flexible soft ether group segment. The castor oil-modified polyol and the polyethylene glycol diglycidyl ether produce a good synergistic effect and can be further cross-linked with the diisocyanate. The prepared isocyanate acrylate has a network-like interwoven molecular structure. The UV moisture-curing adhesive prepared from the isocyanate acrylate prepared in this way has good tackiness and good lamination stability. The inhibitor has good control over the reaction, and the storage stability of the prepared isocyanate acrylate is improved.

[0023] Preferably, the isocyanate acrylate is prepared by the following steps: adding diisocyanate, hydroxy acrylate, castor oil modified polyol and polyethylene glycol diglycidyl ether to a reaction device, stirring evenly, adding a catalyst and an inhibitor, and reacting for 2-3 hours at a temperature of 70-80°C and a vacuum degree of -0.8MPa--1.0MPa to obtain isocyanate acrylate.

[0024] By adopting the above technical scheme, isocyanate acrylate with isocyanate active groups having stable performance is prepared under better reaction conditions.

[0025] Preferably, the acrylate monomers are composed of isobornyl acrylate, lauric acid acrylate and cyclotrimethylolpropane formal acrylate in a weight ratio of (1.5-2):(0.8-1.2):(0.3-0.6).

[0026] By adopting the above technical solution and polymerizing the above acrylate monomer, the prepared UV moisture curing adhesive has moderate hardness as well as good flexibility and bonding stability.

[0027] Preferably, the stabilizer is composed of hydroxy polyether modified polydimethylsiloxane and γ-methacryloxypropyltrimethoxysilane in a weight ratio of (0.2-0.5):1.

[0028] By adopting the above technical scheme, the hydroxyl polyether modified polydimethylsiloxane is a soft silicone structure with siloxane as the main body and containing polyether segments and hydroxyl active groups, and γ-methacryloxypropyltrimethoxysilane is a silane coupling agent containing organic functional groups. The hydroxyl polyether modified polydimethylsiloxane and γ-methacryloxypropyltrimethoxysilane are compounded in a preferred ratio. As a stabilizer, the dispersion stability of each component in the system can be improved, and a good synergistic effect can be produced with the polyurethane acrylate and isocyanate acrylate system. The UV moisture curing adhesive prepared in this way has good curing cross-linking stability and temperature resistance stability, thereby improving the adhesion of the UV moisture curing adhesive film formed after curing to electronic components.

[0029] Preferably, the dehydrating agent is composed of p-toluenesulfonyl isocyanate and vinyl trimethoxy silane in a weight ratio of 1:(0.1-0.3).

[0030] By adopting the above technical solution, the optimal ratio of p-toluenesulfonyl isocyanate and vinyltrimethoxysilane has a higher activity in reacting with water, which can quickly consume the moisture in the system, thereby improving the storage stability of the prepared UV moisture-curing adhesive.

[0031] Preferably, the photoinitiator is any one or a combination of 2-hydroxy-2-methylpropiophenone, 1-hydroxycyclohexyl phenyl ketone, and ethyl 2,4,6-trimethylbenzoylphenylphosphonate.

[0032] By adopting the above technical solution, the above photoinitiator has good photoinitiating efficiency, so that the prepared UV moisture curing adhesive can stably perform cross-linking and curing.

[0033] Preferably, the antioxidant is any one or a combination of tris(2,4-di-tert-butylphenyl)phosphite and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate.

[0034] By adopting the above technical solution, the above antioxidant has good antioxidant performance, can improve the milk aging performance of the UV moisture-cured adhesive film formed by curing, and improve the service life.

[0035] In a second aspect, the present application provides a method for preparing a UV moisture curing adhesive for electronic components, using the following technical solution:

[0036] A method for preparing a UV moisture curing adhesive for electronic components comprises the following steps:

[0037] S1, adding acrylate monomer, stabilizer and antioxidant into a reaction device, and performing vacuum stirring to obtain a mixture A;

[0038] S2, adding polyurethane acrylate to mixture A, stirring under vacuum, to obtain mixture B;

[0039] S3, adding a dehydrating agent to the mixture B, stirring under vacuum, to obtain a mixture C;

[0040] S4, adding isocyanate acrylate to mixture C, stirring under vacuum, to obtain mixture D;

[0041] S5. Add a photoinitiator and a catalyst to the mixture D, stir under vacuum, and prepare a UV moisture curing adhesive.

[0042] By adopting the above technical scheme, under the condition of vacuum stirring throughout the process, the acrylate monomer, stabilizer and antioxidant are first mixed, then polyurethane acrylate is added and mixed, and then a desiccant is added to remove excess water, and then isocyanate acrylate is added to make it difficult for isocyanate acrylate to react with water in the system, thereby improving the stability of production, and finally a photoinitiator and a catalyst are added to obtain a UV moisture-curing adhesive with a stable system and storage stability.

[0043] Preferably, in the steps S1-S4, the vacuum degree of vacuum stirring is -0.8MPa--1.0MPa, and in the step S3, after adding the dehydrating agent, the stirring time is 1.5-2.5h, and the moisture content is stirred and controlled to be less than 500ppm.

[0044] By adopting the above technical solution, vacuum stirring can improve the mixing uniformity between the raw materials, while reducing the introduction of water impurities. Adding a dehydrating agent, controlling the optimal stirring time, and fully stirring to reduce the moisture content to below 500ppm is to prevent the later added isocyanate acrylate from reacting with moisture and improve the stability of the UV moisture curing adhesive.

[0045] In summary, this application has the following beneficial effects:

[0046] 1. The UV moisture curing adhesive for electronic components of the present application uses polyurethane acrylate and isocyanate acrylate as the main body. Under the action of catalyst, photoinitiator, stabilizer and acrylic monomer, the prepared UV moisture curing adhesive can stably cross-link and cure under ultraviolet light and room temperature conditions, and can be applied to thin and light electronic products. The UV moisture curing adhesive film formed after curing has a relatively moderate initial viscosity, good adhesion to electronic components, and is not prone to unstable bonding during long-term use, thereby improving the service life of electronic products.

[0047] 2. By adding castor oil-modified polyol and polyethylene glycol diglycidyl ether to the reaction system of diisocyanate and hydroxy acrylate under the action of a catalyst and an inhibitor, castor oil-modified polyol and polyethylene glycol diglycidyl ether produce a good synergistic effect and can be further cross-linked with diisocyanate. The obtained isocyanate acrylate has a network-like interwoven molecular structure. The UV moisture-curing adhesive prepared from the isocyanate acrylate has good tack retention and good bonding stability.

[0048] 3. By using a better ratio of hydroxy polyether modified polydimethylsiloxane and γ-methacryloxypropyltrimethoxysilane as stabilizers, it can produce a better synergistic effect with polyurethane acrylate and isocyanate acrylate, and can better improve the dispersion stability of each component in the system. The UV moisture curing adhesive prepared in this way has better curing cross-linking stability and temperature resistance stability, thereby improving the adhesion of the UV moisture curing adhesive film formed after curing to electronic components.

[0049] 4. The preparation process of the present application is to first mix the stabilizer, acrylate monomer, antioxidant and polyurethane acrylate evenly, then add the desiccant and stir thoroughly to remove excess water, and then add isocyanate acrylate, photoinitiator and catalyst to mix. The UV moisture curing adhesive prepared in this way has good stability. DETAILED DESCRIPTION

[0050] The present application is further described in detail below with reference to the embodiments.

[0051] Preparation Example of Isocyanate Acrylate

[0052] Preparation Example 1

[0053] Preparation Example 1 discloses an isocyanate acrylate, which is prepared by the following steps:

[0054] 2.5 kg of hexamethylene diisocyanate as diisocyanate, 1 kg of hydroxyethyl acrylate as hydroxy acrylate, 0.2 kg of castor oil-modified polyol and 0.05 kg of polyethylene glycol diglycidyl ether were added to a reactor, stirred at a stirring rate of 300 r / min for 20 min, and after stirring evenly, 5 g of stannous octoate as a catalyst and 2 g of p-hydroxyanisole as a polymerization inhibitor were added, and the mixture was reacted for 2-3 h at a temperature of 70-80° C. and a vacuum degree of -0.8 MPa--1.0 MPa to obtain isocyanate acrylate;

[0055] Castor oil modified polyol is produced by Anshan Chuangye Bio-New Material Technology Co., Ltd., model CY-009, hydroxyl value 215-235 mgKOH / g, viscosity 1200-1900 mPa.s / 20°C, functional group number 2.5; polyethylene glycol diglycidyl ether: content 99%, CAS number 39443-66-8, density 1.14 g / ml, 25°C, epoxy value 0.35-0.40 eq / 100g.

[0056] Preparation Example 2-3

[0057] The difference between Preparation Example 2-3 and Preparation Example 1 is that the amount of raw materials used and the preparation conditions are different, see Table 1 below for details.

[0058] Table 1 Raw material dosage and preparation conditions of Preparation Examples 1-3

[0059]

[0060] Preparation Comparative Example 1

[0061] The difference between Preparation Example 1 and Preparation Example 3 is that an equal amount of polyethylene glycol diglycidyl ether is replaced by castor oil-modified polyol, and the rest is the same as Preparation Example 1.

[0062] Preparation Comparative Example 2

[0063] The difference between Preparation Comparative Example 2 and Preparation Example 3 is that the castor oil-modified polyol is replaced with an equal amount of 1,4-butanediol, and the rest is the same as Preparation Example 3.

[0064] Preparation Comparative Example 3

[0065] The difference between Preparation Comparative Example 3 and Preparation Example 3 is that castor oil-modified polyol and polyethylene glycol diglycidyl ether are replaced by hydroxyethyl acrylate in equal amounts, and the rest is the same as Preparation Example 3.

[0066] Example

[0067] Example 1

[0068] Example 1 discloses a UV moisture curing adhesive for electronic components, which is prepared by the following steps:

[0069] S1, adding acrylate monomers consisting of 1.731 kg of isobornyl acrylate, 0.923 kg of lauric acid acrylate and 0.346 kg of cyclotrimethylolpropane formal acrylate, 0.2 kg of γ-methacryloxypropyltrimethoxysilane as a stabilizer and 0.01 kg of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate as an antioxidant into a reactor, and stirring for 20 min under a vacuum degree of -0.8 MPa to obtain a mixture A;

[0070] S2, adding 2.5 kg of polyurethane acrylate to mixture A, stirring for 20 min under a vacuum degree of -0.8 MPa to obtain mixture B;

[0071] S3, adding 0.1 kg of p-toluenesulfonyl isocyanate as a dehydrating agent to the mixture B, stirring for 1.5 h under a vacuum degree of -0.8 MPa, stirring until the water content is 450 ppm, stopping stirring, and obtaining a mixture C;

[0072] S4, adding 0.6 kg of commercially available isocyanate acrylate to the mixture C, stirring for 20 min under a vacuum degree of -0.8 MPa to obtain a mixture D;

[0073] S5, adding a photoinitiator consisting of 0.2 kg 2-hydroxy-2-methylpropiophenone and 0.1 kg ethyl 2,4,6-trimethylbenzoylphenylphosphonate and 0.005 kg WCAT-WS2 catalyst to the mixture D, stirring for 10 min under a vacuum degree of -0.8 MPa to obtain a UV moisture curing adhesive;

[0074] The polyurethane acrylate in Example 1 is derived from Shanghai Huiyan New Materials Co., Ltd. HY-7902, 2 functional groups, density (g / cm3, 25°C): 1.1±0.1; the catalyst WCAT-WS2 is derived from Guangzhou Yourun Synthetic Materials Co., Ltd.; the isocyanate acrylate is derived from Kmik, ethyl isocyanate acrylate, CAS No. 13641-96-8, content 98%.

[0075] Example 2-3

[0076] The difference between Example 2-3 and Example 1 is that the amount of raw materials used and the preparation conditions are different, see Table 2 below for details.

[0077] Table 2 Raw material dosage and preparation conditions of Examples 1-3

[0078]

[0079]

[0080]

[0081] Embodiment 4-9

[0082] The difference between Examples 4-9 and Example 3 is that the sources of isocyanate acrylate are different, see Table 3 below for details.

[0083] Table 3 Sources of isocyanate acrylates in Examples 4-9

[0084] Example Source of Isocyanate Acrylate Example 4 Preparation Example 1 Example 5 Preparation Example 2 Example 6 Preparation Example 3 Example 7 Preparation Comparative Example 1 Example 8 Preparation Comparative Example 2 Example 9 Preparation Comparative Example 3

[0085] Example 10

[0086] The difference between Example 10 and Example 6 is that the stabilizer is different. The stabilizer in Example 6 is composed of hydroxy polyether modified polydimethylsiloxane and γ-methacryloxypropyltrimethoxysilane in a weight ratio of 0.2:1, and the rest is the same as Example 6; the hydroxy polyether modified polydimethylsiloxane is derived from Kramar 8530H, with a hydroxyl content of 1.5%, a viscosity of 1000-5000, and 25°C / cps.

[0087] Embodiment 11

[0088] The difference between Example 11 and Example 10 is that the stabilizer in Example 11 is composed of hydroxy polyether modified polydimethylsiloxane and γ-methacryloxypropyltrimethoxysilane in a weight ratio of 0.5:1, and the rest is the same as Example 11.

[0089] Example 12

[0090] The difference between Example 12 and Example 11 is that the dehydrating agent is different. The dehydrating agent in Example 12 is composed of p-toluenesulfonyl isocyanate and vinyl trimethoxy silane in a weight ratio of 1:0.3, and the rest is the same as Example 11.

[0091] Comparative Example

[0092] Comparative Example 1

[0093] The difference between Comparative Example 1 and Example 1 is that an equal amount of polyurethane acrylate is replaced by isocyanate acrylate, and the rest is the same as Example 1.

[0094] Comparative Example 2

[0095] The difference between Comparative Example 2 and Example 1 is that polyurethane acrylate and isocyanate acrylate are replaced by dual-curing polyurethane acrylate from Allnex EBECRYL 4397, with a viscosity of 11000S and a content of 99%. The rest is the same as Example 1.

[0096] Comparative Example 3

[0097] The difference between Comparative Example 3 and Example 1 is that the stabilizer is replaced by isocyanate acrylate in equal amount, and the rest is the same as Example 1.

[0098] Performance testing

[0099] The following performance tests were conducted on the UV moisture curing adhesives for electronic components prepared in Examples 1-12 and Comparative Examples 1-3: (1) Tensile shear strength test

[0100] According to the test method in GB / T 7124-2008 "Determination of tensile shear strength of adhesives", the coating thickness of UV moisture curing adhesive was controlled to be 20±0.1μm, and the test plate coated with UV moisture curing adhesive was placed in a UV box for curing. The light source used was 365nm ultraviolet light, and the curing energy was 1500mj / cm 2 , the curing time is 5s, and then placed in a constant temperature and humidity box with a temperature of 25°C and a humidity of 45% for 6h, and then restored to room temperature (25°C). The tensile testing machine is used for testing, and the tensile shear strength (unit: MPa) is tested and recorded, which is recorded as the first tensile shear strength;

[0101] (2) Adhesion test

[0102] According to the test method in GB / T 7124-2008 "Determination of tensile shear strength of adhesives", the coating thickness of UV moisture curing adhesive is controlled to be 20±0.1μm, and the test plate coated with UV moisture curing adhesive is placed in a UV box for curing. The light source used is 365nm ultraviolet light, and the curing energy is 1500mj / cm 3 , the curing time is 5s, and then placed in a constant temperature and humidity chamber at a temperature of 25°C and a humidity of 45%, cured for 3h, and then restored to room temperature (25°C), placed in a constant temperature and humidity chamber at a temperature of 75°C and a humidity of 50%, tested for 7 days, and then restored to room temperature (25°C), tested and recorded the tensile shear strength (unit: MPa), recorded as the second tensile shear strength.

[0103] The following are the performance test data of the UV moisture curing adhesive for electronic components of Examples 1-12 and Comparative Examples 1-3, see Table 4 below for details.

[0104] Table 4 Performance test data of Examples 1-12 and Comparative Examples 1-3

[0105]

[0106] Combining Examples 1-3 and Examples 4-9, Comparative Examples 1-2 and Table 4, it can be seen that the isocyanate acrylate of the present application is added to the system, and the bonding performance and persistent adhesion of the obtained UV moisture curing adhesive are good, and the lamination is stable. Compared with Example 3, the persistent adhesion of Example 6 is improved by 0.87 MPa, and after the weather resistance persistent adhesion test, the tensile shear strength of Example 6 is increased from the original 0.75 MPa to 5.05 MPa, an increase of 4.3 MPa, while that of Example 3 is increased from the original 0.45 MPa to 4.18 MPa, an increase of 3.73 MPa. The persistent adhesion improvement rate in Example 6 is higher. In Comparative Example 1, polyurethane acrylate is replaced with isocyanate acrylate in equal amounts, and in Comparative Example 2, polyurethane acrylate and isocyanate acrylate are replaced with commercially available dual-curing polyurethane acrylate in equal amounts, and the persistent adhesion of the obtained UV moisture curing adhesive is significantly reduced.

[0107] Combining Examples 1-6 and Examples 10-11, Comparative Example 3 and Table 4, it can be seen that the use of the preferred ratio of hydroxyl polyether modified polydimethylsiloxane and γ-methacryloxypropyltrimethoxysilane in the present application as a stabilizer can further improve the adhesion and tackiness of the prepared UV moisture curing adhesive. In Comparative Example 3, the stabilizer is replaced with isocyanate acrylate. Compared with Example 1, both the adhesion and tackiness are reduced, which may be due to the lack of dispersion and further cross-linking of the stabilizer. It can be seen that the polyurethane acrylate, isocyanate acrylate and stabilizer of the present application have a good synergistic effect.

[0108] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A UV moisture curing adhesive for electronic components, characterized in that: Made from the following raw materials in parts by weight: Polyurethane acrylate 25-45 parts Isocyanate acrylate 6-15 parts Acrylate monomer 30-50 parts Photoinitiator 3-8 parts Stabilizer 2-6 parts 1-2 parts of dewatering agent Antioxidant 0.1-0.6 parts Catalyst 0.05-0.2 parts; The isocyanate acrylate is prepared from the following raw materials in parts by weight: 25-35 parts of diisocyanate Hydroxyacrylate 10-20 parts 2-4 parts of castor oil modified polyol Polyethylene glycol diglycidyl ether 0.5-2 parts Catalyst 0.05-0.15 parts Inhibitor 0.02-0.08 parts; The stabilizer is composed of hydroxy polyether modified polydimethylsiloxane and γ-methacryloxypropyltrimethoxysilane in a weight ratio of (0.2-0.5):1; The isocyanate acrylate is prepared by the following steps: adding diisocyanate, hydroxy acrylate, castor oil modified polyol and polyethylene glycol diglycidyl ether into a reaction device, stirring evenly, adding a catalyst and a polymerization inhibitor, reacting for 2-3 hours at a temperature of 70-80° C. and a vacuum degree of -0.8 MPa--1.0 MPa to prepare isocyanate acrylate; The acrylate monomer is composed of isobornyl acrylate, lauric acid acrylate and cyclotrimethylolpropane formal acrylate in a weight ratio of (1.5-2): (0.8-1.2): (0.3-0.6); The dewatering agent is composed of p-toluenesulfonyl isocyanate and vinyl trimethoxy silane in a weight ratio of 1:(0.1-0.3).

2. The UV moisture curing adhesive for electronic components according to claim 1, characterized in that: The photoinitiator is any one or a combination of 2-hydroxy-2-methylpropiophenone, 1-hydroxycyclohexyl phenyl ketone, and ethyl 2,4,6-trimethylbenzoylphenylphosphonate.

3. The UV moisture curing adhesive for electronic components according to claim 1, characterized in that: The antioxidant is any one or a combination of tris(2,4-di-tert-butylphenyl)phosphite and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate.

4. A method for preparing a UV moisture curing adhesive for electronic components as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: S1, adding acrylate monomer, stabilizer and antioxidant into a reaction device, and performing vacuum stirring to obtain a mixture A; S2, adding polyurethane acrylate to mixture A, stirring under vacuum, to obtain mixture B; S3, adding a dehydrating agent to the mixture B, stirring under vacuum, to obtain a mixture C; S4, adding isocyanate acrylate to mixture C, stirring under vacuum, to obtain mixture D; S5. Add a photoinitiator and a catalyst to the mixture D, stir under vacuum, and prepare a UV moisture curing adhesive.

5. The method for preparing a UV moisture curing adhesive for electronic components according to claim 4, characterized in that: In the steps S1 to S4, the vacuum degree of vacuum stirring is -0.8 MPa to 1.0 MPa. In the step S3, after adding the dehydrating agent, the stirring time is 1.5 to 2.5 hours, and the water content is stirred and controlled to be less than 500 ppm.

Citation Information

Patent Citations

  • Photo-moisture curing adhesive with high-efficiency moisture barrier property and ultralow water absorption

    CN110885664A

  • Curable resin composition

    JP6791319B1